After 1989 - Dahrendorf, Ralf. author. aut Link
VII, 179 p.
Keywords: The essays assembled in this volume are a thoughtful and lively commentary on Europe after the revolution of 1989. Must revolutions fail? Certainly, the open society has its own problems, not least that of citizens in search of meaning. The Good Society has to square the circle of prosperity, civility and liberty. Social science can help us understand what needs to be done, and intellectuals have a responsibility to initiate and accompany change. All this raises questions for Europe which extend far beyond the all too narrow confines of the European Union.